The Use of Touch DNA Analysis in Forensic Identification Focusing on STR CODIS LOCI THO1, CSF1PO and TPOX - Ahmad Yudianto1 , Simon Martin Manyanza Nzilibili2 , Pudji Harjanto2 , Fery Setiawan2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction:Identification through DNA analysis is an accurate diagnostic tool. DNA analysis is via Variable Number of Tandem Repeat (VNTR) and Restriction Fragment Length Polymorphisms (RFLP). Up to date, blood spots/blood, sperm spots, vaginal swabs, buccal swabs and bones are specimens that are widely used in the field of forensics for DNA analysis. At the crime scene, the perpetrator’s skin may accidentally be in contact with surrounding objects thereby transferring trace evidence to the objects. Method and Materials: Laboratory observation to demonstrate identification through DNA isolation from the objects that are touched (touch DNA), using the STR CODIS locus, with a momentary research design. DNA was isolated from buccal swabs and swab properties (watches and mobile phones) from volunteers who have signed the consent form. A total of ten samples were used in this study. Results and Discussion: Mean levels of DNA [UV-Visible Spectrophotometer] buccal swab: 167.89 ± 85.71 µg / ml, watch swab: 59.19 ± 5.58 µg / ml, mobile swab: 38.09 ± 2.12 µg / ml and the purity of the buccal swab DNA: 1.79 ± 0.71, the watch swab: 1.69 ± 0.76, the mobile swab:1,53 ± 0,56. Visualization of PCR products onPolyacrylamide Agarose Composite Gel Electrophoresis [PAGE] stained with Silver and amplified using the standard primers THOI, TPOX and CSF1POfor STR CODIS showed a 100% detection of amplicons. Allele profiles on all samples of STR CODIS were a match or identical to the positive control K562. Conclusion:Property (handphone and watch) swabs can be used as alternative materials in forensic identification using Touch DNA analysis. It was able to be isolated and amplified by using Polymerase Chain Reaction on the STR CODIS loci THO1, CSF1PO and TPOX